Studi Pemikiran MM. Adzami Ahli Hadist Melawan Orientalis - Muhammad Aly Mahmudi (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
Hadith is the primary source in Islamic studies, in addition to being a legal source of hadith function as well as a track record of evidence of reference in all Islamic studies. The importance of this hadith becomes an interesting study of both Islam and orientalists, , the form of study is also variative and always develops according to the existing context. Josept Schat is a non-Muslim who studied his theory to inspire Islamic thinkers to give a defensive to some of the allegations that became the result of the study. Muhammad Musthofa Al-Adzami is a hadith expert who dares to provide authentic evidence of the existence of hadith even he can prove the original manuscript of hadith as a rebuttal to the study of deviant hadith. This paper seeks to give an overview of Adzami's thinking in criticalizing orientalist studies of hadith.